The theses for PhD degree - article Editorial (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2009)
L.A. Semenyuk – Erosive-ulcerative form of gastroesophageal reflux disease in children: risk factors, clinical presentation, diagnostics and treatment.O.S. Shifrin – Features of medical approach in patients with chronic pancreatitis of moderate severity of various etiology.Ye.Yu. Shkatova – Mechanisms of intractable gastroduodenal ulcer development. Advancement of multifactor prediction system and pathogenic treatment.